Bilateral concha bullosa with right sided extensive rhinolith: a case report - Prinja, Sumit; Davessar, Jailal; Singh, Gurbax; Jindal, Simmi; Bali, Alisha (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Anatomic variations of the paranasal sinuses can lead to various diseases per se. The paranasal sinus anatomy should be carefully examined prior to performing endoscopic sinus surgery in terms of both existent pathologies and anatomic variations. The anatomy of the paranasal sinuses and its variations have gained importance, along with advances in coronal paranasal sinus computed tomography and extensive use of endoscopic sinus surgery. Rhinolith is a mass resulting from calcification of an endogenous or exogenous nidus within the nasal cavity. It is an uncommon disease that may present asymptomatically or cause symptoms like headache and nasal obstruction. A 24 year old woman was admitted in ENT department of GGS Medical College and Hospital, Faridkot with complaints of nasal obstruction, anosmia and headache persisting for 5 years. Right sided rhinolith was detected on anterior rhinoscopy. Bilateral concha bullosa with right sided rhinolith was reported on preoperative paranasal computed tomography scan. It is known that the paranasal sinuses have a number of anatomical variations. Sometimes severe anatomic variations predispose to rhinosinusitis. Herein we report a rare case, along with a review of the literature, to emphasize that severe anatomical variations should not be ignored.